Room-Temperature Phosphorescent Co-Crystal Showing Direct White Light and Photo-Electric Conversion - Yang, Xiao-Gang; Qin, Wen-Jing; Zhang, Ji-Rui; Tian, Xu-Ke; Fan, Xin; Ma, Lu-Fang; Yan, Dongpeng (Frontiers in Chemistry, 2021)
The development of molecular crystalline materials with efficient room-temperature phosphorescence has been obtained much attention due to their fascinating photophysical properties and potential applications in the fields of data storage, bioimaging and photodynamic therapy. Herein, a new co-crystal complex [(DCPA)(AD)2] (DCPA = 9,10-di(4-carboxyphenyl)anthracene); AD = acridine) has been synthesized by a facile solvothermal process. Crystal structure analysis reveals that the co-crystal possesses orderly and alternant arrangement of DCPA donors and AD acceptors at molecular level. Fixed by strong hydrogen bonds, the DCPA molecule displays seriously twisty spatial conformation. Density functional theory (DFT) calculations show well separation of HOMO and LUMO for this co-crystal system, suggesting the efficient triplet excitons generation. Photoluminescence measurements show intensive cyan fluorescence (58.20 ns) and direct white phosphorescence (325 μs) emission at room-temperature. The transient current density–time curve reveals a typical switching electric response under the irradiation of simulated light, reveal that the [(DCPA)(AD)2] co-crystal has a high photoelectric response performance.